Suppressive effects of metformin on T-helper 1-related chemokines expression in the human monocytic leukemia cell line THP-1. (2nd October 2018) - Chen, Yen-Chun; Kuo, Chang-Hung; Tsai, Ying-Ming; Lin, Yi-Ching; Hsiao, Hui-Pin; Chen, Bai-Hsiun; Chen, Yi-Ting; Wang, Shih-Ling; Hung, Chih-Hsing
ABSTRACT: Purpose of the study : Type 1 and type 2 diabetes mellitus (DM) are chronic T-cell-mediated inflammatory diseases. Metformin is a widely used drug for type 2 DM that reduces the need for insulin in type 1 DM. However, whether metformin has an anti-inflammatory effect for treating DM is unknown. We investigated the anti-inflammatory mechanism of metformin in the human monocytic leukemia cell line THP-1. Materials and methods : The human monocytic leukemia cell line THP-1 was pretreated with metformin and stimulated with lipopolysaccharide (LPS). The production of T-helper (Th)-1-related chemokines including interferon-γ-induced protein-10 (IP-10) and monocyte chemoattractant protein-1 (MCP-1), Th2-related chemokine macrophage-derived chemokine, and the proinflammatory chemokine tumor necrosis factor-α was measured using enzyme-linked immunosorbent assay. Intracellular signaling pathways were investigated using Western blot analysis and chromatin immunoprecipitation assay. Results : Metformin suppressed LPS-induced IP-10 and MCP-1 production as well as LPS-induced phosphorylation of c-Jun N-terminal kinase (JNK), p38, extracellular signal-regulated kinase (ERK), and nuclear factor-kappa B (NF-κB). Moreover, metformin suppressed LPS-induced acetylation of histones H3 and H4 at the IP-10 promoter. Conclusions : Metformin suppressed the production of Th1-related chemokines IP-10 and MCP-1 in THP-1 cells. Suppressive effects of metformin on IP-10 production might be attributed at least partially to the JNK, p38, ERK, and NF-κB pathways as well as to epigenetic regulation through the acetylation of histones H3 and H4. These results indicated the therapeutic anti-inflammatory potential of metformin.